Antegrade jejunogastric intussusception and common bile duct stones at 14 months after gastrectomy and cholecystectomy: A case report. (2017) - Miura, Yuichi; Uemura, Takuji; Sato, Koichiro; Abe, Takayuki; Akada, Tetsuya; Ito, Soichi; Yamana, Hiroki; Kato, Hirotaka
Highlights: Jejunogastric intussusception occurred after distal gastrectomy followed by Roux-en Y reconstruction. Common bile duct stone occurred after prophylactic cholecystectomy and distal gastrectomy. Intussusception and common bile duct stone both could occur simultaneously after gastrectomy. Abstract: Introduction: Intussusception after gastrectomy is a minor complication after gastrectomy, while common bile duct stone (CBD) is also a rare complication post cholecystectomy. We report a case that simultaneously caused both intussusception and CBD stone following gastrectomy with prophylactic cholecystectomy. Case presentation: A 74-year-old woman underwent distal gastrectomy with Roux-en-Y reconstruction and prophylactic cholecystectomy for gastric cancer. After 14 months, the patient reported nausea and vomiting. Abdominal computed tomography scanning showed antegrade intussusception of the Roux limb of the gastrojejunostomy and calculi in the common bile duct, with a diagnosis of jejunogastric intussusception and common bile duct stones. The patient was hospitalized and endoscopic examination was performed on day 3. Endoscopic treatment did not resolve the intussusception, which also obstructed the bile duct stones. Elective surgery was performed on day 10, in which the invaginated Roux limb of the gastrojejunostomy was resected after manual reinstatement to its original position. This was followed by open exploration of the common bile duct and T-tube drainage. The patient was discharged 25 days post- surgery. Discussion: Jejunogastric intussusception and CBD stone may require operative management, although the operation could be elective after sufficient examination and preparation. Conclusion: Jejunogastric intussusception and bile duct stones are rare after distal gastrectomy, physicians should be alerted to the possibility of these complications.